0.91 V reference, 3.3 ppm/°C Sub-BGR with second-order compensation and improved PSRR - Chokkakula Ganesh; Satheesh Kumar S; A. Shanthi; Sk Shoukath Vali (Scientific Reports)
Abstract This work introduces the design and analysis of a Bandgap Reference (BGR) circuit with better temperature stability and reduced process variation. The second-order compensation method is implemented for design through an optimized error amplifier and a resistor network with a significantly better temperature coefficient performance. The startup mechanism is carefully designed for ensured strong and stable circuit performance under every variation of process-voltage-temperature (PVT). The proposed BGR is compared with conventional methods such as CM-BGR, Cascaded CM-BGR, Operational Amplifier based-BGR, and Sub-BGR with respect to Temperature Coefficient (TC), Power Supply Rejection Ratio (PSRR), and line regulation. The proposed Sub-BGR is shown to provide 3.33 ppm/°C (58.97–78.79% less) temperature coefficient, 1.12×–6.02× improvement in PSRR, and 96% improved line regulation with 723 µV variation, thus showing improved performance compared to Operational Amplifier based-BGR and Sub-BGR techniques, rendering the proposed BGR highly appropriate for high-precision analog and mixed-signal applications. The proposed BGR is simulated and implemented by Synopsys custom compile using 32 nm CMOS technology.